Correction to: Influence of a Planning Intervention on Physical Activity Behavior: The Moderating Role of Intentions and Executive Functions in a Randomized Controlled Trial - Ines Pfeffer; Tilo Strobach (International Journal of Behavioral Medicine, 2021)
A correction to this paper has been published: https://doi.org/10.1007/s12529-021-09980-2